Implementasi 4 Pilar Visi Pendidikan di Indonesia: Visi Pendidikan Berbasis Agama, Filsafat, Psikologi dan Sosiologi - Usep Setiawan; Ujang Nurjaman; Faiz Karim Fatkhulloh; Arman Paramansyah (Jurnal Dirosah Islamiyah, 2022)
Education is the main basis in the life of every human being, with a good education a good society will grow as well. In education, of course, it has a vision of various forms for the main goals to be achieved. The concept of the vision of education based on religion, philosophy, psychology and sociology is used as a model for the implementation of education in Indonesia in order to achieve the goals of education as a whole within the framework of the intellectual life of the nation. The purpose of this study was to find out how the implementation of the four pillars of the vision of education in terms of religion, philosophy, psychology and sociology. Theoretically, the application of the four pillars of the vision of religion-based education provides spiritual reinforcement to always be submissive and obedient to the Shari'a and hold fast to self-confidence in carrying out life. Philosophically it teaches humans to be mature in acting and wise in behavior, psychologically teaches about gentleness in educating so that they can adjust between a person's condition according to their respective maturity, and sociologically it is taught to how humans are good at socializing well with the wider community through values. - educational values ​​applied by educated beings. This study uses a descriptive qualitative approach with analytical methods based on a literature review in accordance with the discussion. With the implementation of the vision of education in terms of religion, philosophy, psychology and sociology, it is hoped that it will be able to realize quality and highly competitive education and be able to realize the noble ideals of the Indonesian nation. Keywords: Educational Vision, Religion, Philosophy, Psychology and Sociology